Kajian Meta-Analisis Hubungan antara Self Esteem dan Kesejahteraan Psikologis - Yeni Triwahyuningsih (Buletin Psikologi, 2017)
In the last decade,the research on the relationship between self esteem and psychological well - being has increased. The wellbeing that distinguishes between hedonic and eudaimonic ideology is widely used in research and has been empirically supported by experts from different cultures. The results of the study about correlation between self-esteem and psychological wellbeing showed varying results. The purpose of this study was to determine the relationship between self esteem and psychological wellbeing through a meta-analysis study. The total study used was 24. Meta-analysis was performed based on sampling error. The results of the meta-analysis show generally that between self-esteem and psychological well-being is low. Correlation based on sampling error is 0.269, withi n the 95% confidence interval limit. The limited number of studies in the study may be a weakness. The accuracy of meta-analysis depends on the total sample used